A Stairs Evacuation Model Considering the Pedestrian Merging Flows - Xia Zhong Zheng; Dan Tian; Ming Zhang; Chaoran Hu; Liyang Tong (Discrete Dynamics in Nature and Society)
Pedestrian merging flows are common in a stairs evacuation process, which involves complex interactions among pedestrians that substantially restrict the efficiency of the stairs evacuation process. Analyzing the pedestrian merging flows process and improving the efficiency of stairs evacuation are urgent and essential tasks. A novel simplified stairs evacuation model for simulating and analyzing the stairs evacuation process, which considers the impact of merging flows, is proposed in this process. The dynamic pedestrian output rate of a floor platform is calculated by the number of pedestrians on the floor platform. The merging ratio determined by the design size of stairs is adopted to determine the ratio between the stairs pedestrian flow and the floor pedestrian flow in the pedestrian output rate of the floor platform. To evaluate the stairs evacuation process is divided into three stages based on the pedestrian merging flows process, and the evacuation time at each stage is computed by the dynamic pedestrian output rate of the floor platform. The stairs evacuation capacity is calculated by the evacuation time and the number of pedestrians. A case study of a six-floor building evacuation is investigated, and the reliability and feasibility of the proposed model is verified. By establishing different merging ratios, the optimal merging ratio is obtained by comparing the evacuation capacities of different merging ratios, which provides a reference of stairs design for designers.